Designing the Arabic Crossword Puzzles for the First, Second, and Third Grade of the “Mambaul Ulum” Islamic Elementary School Malang - Nurul Hidayati; Muhammad Lukman Arifianto; Mochammad Rizal Ramadhan (Al-Arabi : Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2020)
Crossword puzzle is a game whose gameplay is to fill in the empty spaces in a box with letters to form a word that matches the instructions. This game is one of the best ways to develop student’s ability to multiply vocabulary and they would feel enthusiasm in participating in the teaching process. The elementary school students need some attractive and enjoyable things in their learning and teaching process. The materials presented in the vocabulary related to the materials presented by the teacher in the first to the third grade of the primary school. By using this game, the students are not limited to completing the questions only, but it can also sharpen the cognitive ability of the students. The development research adopted the modified Borg and Gall research model. The results of this research were applied to students in the third grade of Mambaul Ulum Islamic Elementary School at Malang. The result of this development is (1) an Arabic crossword puzzle game to teach the Arabic language and its evaluation consisting of the output page in which the login, the user guide, the developed team pictures, the pictures of the supervisor group as well as the experts. On the play page, there are spaces and questions and the result of the students and this programming is complemented by the dictionary and (2) the result investigation on this method shows that it is effective. Teka-teki silang merupakan permainan yang cara mainnya adalah dengan mengisi kolom yang  kosong dengan huruf-huruf agar membentuk kata yang sesuai dengan petunjuknya. Teka-teki silang adalah salah satu cara terbaik untuk mengembangkan kemampuan siswa dalam memperbanyak kosakata, dan dengan cara ini siswa merasa antusias untuk berpartisipasi dalam proses pengajaran. Alasan pemilihan metode ini karena siswa sekolah dasar masuk dalam  masa kanak-kanak dimana mereka membutuhkan hal-hal yang menarik dan menyenangkan dalam proses pembelajaran karena tidak mampu memusatkan fokusnya pada satu hal. Pengembangan teka-teki silang sebagai sarana pengajaran dan evaluasi bahasa Arab memberikan manfaat bagi guru dan siswa bahasa Arab. Materi yang disajikan dalam kosakata terkait dengan materi yang disampaikan oleh guru pada kelas satu sampai dengan kelas tiga sekolah dasar Dengan metode ini siswa tidak sebatas menyelesaikan soal saja, tetapi metode ini dapat mengasah kemampuan kognitif siswa. Penelitian pengembangan menganut model penelitian Borg and Gall yang telah dimodifikasi. Hasil penelitian ini diterapkan pada siswa kelas III MI Mambaul Ulum Pakis. Hasil dari pengembangan ini adalah (1) pengembangan teka-teki silang untuk pembelajaran dan evaluasi bahasa Arab terdiri dari halaman keluaran yang di dalamnya terdapat halaman login, petunjuk penggunaan, gambar tim pengembang media yang dikembangkan, gambar jajaran pembimbing serta validator media. Pada halaman bermain terdapat kotak-kotak kosong dan soal serta hasil belajar siswa, program ini dilengkapi dengan kamus dan (2) hasil penelitian terhadap metode ini menunjukkan bahwa metode ini efektif.